Comparisan of ossicle shape and 12S rRNA gene sequencing techniques for species identification of Gamat-based beche-de-mer from Langkawi Island, Kedah - Kamarudin K.R.; Noor H.M.; Rehan A.M.; Maryam Mohamed Rehan; Nur Zazarina Ramly (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/ERA